2015
DOI: 10.1007/s12192-015-0597-9
|View full text |Cite
|
Sign up to set email alerts
|

Caco-2 cells infected with rotavirus release extracellular vesicles that express markers of apoptotic bodies and exosomes

Abstract: Previously, we showed that infecting human intestinal epithelial cells (Caco-2) with rotavirus (RV) increases the release of extracellular vesicles (EVs) with an immunomodulatory function that, upon concentration at 100,000×g, present buoyant densities on a sucrose gradient of between 1.10 to 1.18 g/ml (characteristic of exosomes) and higher than 1.24 g/ml (proposed for apoptotic bodies). The effect of cellular death induced by RV on the composition of these EV is unknown. Here, we evaluated exosome (CD63, Hsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 47 publications
(110 reference statements)
0
18
0
3
Order By: Relevance
“…We found that a fraction of the rotavirus particles in the cell medium were associated with cellular membranes, in agreement with recent reports that have shown that naked viruses can be released from infected cells within vesicles (22,(40)(41)(42), although in the case of rotavirus the type of association that the viral particles have with membranous structures remains to be determined. In this regard, Barreto et al reported that the structural viral protein VP6 is associated with the exosome marker CDC63 in vitro and in vivo (43), and the same group described that rotavirus infection increases the release of extracellular vesicles (44). While electron microscopy examination of polarized, rotavirus-infected Caco-2 cells did not reveal the presence of extracellular virus within vesicles (15), in this work we found that about 50 to 60% of the extracellular virus was associated with low-density fractions in iodixanol flotation gradients, and the infectivity of the floating virus increased after treatment with Triton X-100, suggesting that a significant fraction of infectious virus is protected by membranous structures.…”
Section: Discussionmentioning
confidence: 99%
“…We found that a fraction of the rotavirus particles in the cell medium were associated with cellular membranes, in agreement with recent reports that have shown that naked viruses can be released from infected cells within vesicles (22,(40)(41)(42), although in the case of rotavirus the type of association that the viral particles have with membranous structures remains to be determined. In this regard, Barreto et al reported that the structural viral protein VP6 is associated with the exosome marker CDC63 in vitro and in vivo (43), and the same group described that rotavirus infection increases the release of extracellular vesicles (44). While electron microscopy examination of polarized, rotavirus-infected Caco-2 cells did not reveal the presence of extracellular virus within vesicles (15), in this work we found that about 50 to 60% of the extracellular virus was associated with low-density fractions in iodixanol flotation gradients, and the infectivity of the floating virus increased after treatment with Triton X-100, suggesting that a significant fraction of infectious virus is protected by membranous structures.…”
Section: Discussionmentioning
confidence: 99%
“…Eukaryotic EVs include (i) exosomes released by exocytosis of multivesicular bodies (usually 50–150 nm), (ii) Microvesicles (MVs, also called microparticles or ectosomes), vesicles around 0.1–1 μm in diameter shed from the plasma membrane, 10–12 and (iii) apoptotic vesicles released by blebbing of apoptotic cells some of which are > 1 μm (apoptotic bodies), 13 , 14 and (iv) large oncosomes released by migratory tumour cells (> 1 µm) 15 , 16 ( Figure 2 ). However, since current isolation protocols only result in relative enrichment of vesicle subpopulations rather than their complete purification, 17 and that no specific markers are available for the subpopulations, it is preferable to refer to purified vesicles as ‘EVs’ and accurately report the purification method used and characteristics present.…”
Section: Isolation and Characterization Of Evsmentioning
confidence: 99%
“…However, rotavirus-infected Sp2/0-Ag14 cells appear to undergo lysis rather than fragmentation into apoptotic bodies. Rotaviruses have been reported to induce apoptosis in Caco-2 cells 53 and oncosis in MA104 cells 54 where virus infection affects cell membrane integrity without inducing DNA fragmentation or formation of apoptotic bodies. On the other hand, rotavirus nonstructural protein NSP1 has been found to suppress apoptotic signaling during the first 6 h post-infection to favor cell survival 55 .…”
Section: Resultsmentioning
confidence: 99%